Determination the opti mum pulping and bleaching conditions for some forest species and evaluation its papers - Mojtaba Goli (Regional Information Center for Science and Technology (RICeST), 2018)
Abstract In recent years, environmental problems of irregular wood harvesting and shortages of raw materials made wood and paper Ind. & country to be faced serious crises. And some researchers and industry experts have led to fundamental and long-term solution for supplying raw materials to these industries. This present study aimed to determine the optimum conditions of pulping and bleaching for several hardwood forest species (as a separate cooking & Combining with 40% popular, 15% beech and hornbeam 45%) and paper evaluation. After preparing CMP in accordance with the terms of an 85% efficiency , Different cooking times (25-60 minutes, temperature of 170 °C, the ratio of L TO W & 7 TO 1 and Making hand sheet with standard 60 gram per square meter, Optical and mechanical properties of paper was evaluated. The results showed that, A species that was used in cooking, Poplar were better in terms of total properties with mechanical and optical properties. Also in Bleaching stage, the tensile strength index is decreased & Burst and tear strength index is improved. The maximum brightness is related to poplar species with mixing and without species and after bleaching the beech is the lowest ones. In both methods the rate of opacity and yellowness is decreased.